The COVID-19 Outbreak as a Trigger Event for Sinophobic Hate Crimes in the United Kingdom - Schumann, Sandy (The British journal of criminology, 2023)
We assessed whether the COVID-19 outbreak in the United Kingdom was associated with a rise in sinophobic hate crimes as well as the temporal distribution of victimization rates. A victimization survey (N = 393) showed that following the first known case of COVID-19 in the United Kingdom, Chinese/East Asian persons had a higher likelihood of being hate crime or incident victims than members of other ethnic minority groups. Specifically, victimization reported by Chinese/East Asian participants reached its highest level in March 2020 (before lockdown); it then dropped significantly after an initial relaxation of restrictions in May 2020. Overall, we documented a temporary, potentially slightly delayed hate crime trigger effect of the COVID-19 outbreak.